Fusion activation by a headless parainfluenza virus 5 hemagglutinin-neuraminidase stalk suggests a modular mechanism for triggering - Bose, Sayantan (National Academy of Sciences, 2012)
The Paramyxoviridae family of enveloped viruses enters cells through the concerted action of two viral glycoproteins. The receptor-binding protein, hemagglutinin-neuraminidase (HN), H, or G, binds its cellular receptor and activates the fusion protein, F, which, through an extensive refolding event, brings viral and cellular membranes together, mediating virus–cell fusion. However, the underlying mechanism of F activation on receptor engagement remains unclear. Current hypotheses propose conformational changes in HN, H, or G propagating from the receptor-binding site in the HN, H, or G globular head to the F-interacting stalk region. We provide evidence that the receptor-binding globular head domain of the paramyxovirus parainfluenza virus 5 HN protein is entirely dispensable for F activation. Considering together the crystal structures of HN from different paramyxoviruses, varying energy requirements for fusion activation, F activation involving the parainfluenza virus 5 HN stalk domain, and properties of a chimeric paramyxovirus HN protein, we propose a simple model for the activation of paramyxovirus fusion.